BERBAGAI MEDIA PEMBUATAN TELUR ASIN TERHADAP KUALITAS ORGANOLEPTIK - Raga Samudera; Abd. Malik (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The purpose of research to know the influence of various media making salted egg on the quality of organoleptic so as to be consideration and information in the use of media making salted egg proper and get better quality. In the implementation of this research design used Completely Randomized Design, which consist of three treatments and five replicates. The treatment is : PG ; salt solutions, PA ; dough ashes rub and PL : dough loam/clay. While test organoleptik salted egg consisted: 1. General appearance, 2. A briny taste egg white and 3. Flavor egg yolk. Data analyzed a sort of descriptive set and models non-parametrik kruskall-walis. The result of this research showed that the treatment significant on general appearance eggs, a briny taste egg white and flavor egg yolk, treatment PG (salt solutions) show the same thing with treatment PA (dough ashes rub) however in contrast to treatment PL (dough loam/clay).